Perceived Value and User Features in Continuance Intention to Use Theme Park Apps - Long, Ting; Suomi, Reima (Association for Information Systems, 2025)
Abstract
Background: While the continuance intention of mobile apps has been extensively researched in tourism contexts, few studies have explored the continuance intention of mobile apps in the specific context of theme park apps from a configurational perspective. This study seeks to bridge this gap by exploring the different combinations of various perceived values and user features that lead to the continuance intention of theme park apps.
Method: The fuzzy-set qualitative comparative analysis (fsQCA) approach is used to examine the combined effect of perceived value (i.e., functional value, convenience value, hedonic value, and social value) and user features (i.e., travel frequency to theme parks and smartphone usage habit) on users’ continuance intention of theme park apps. In addition, the perceived functional value includes five specific functions: real-time information, map navigation, virtual queue, online order, and recommended routes. The proposed conceptual model was tested with survey data gathered in China (N =347).
Results: The results revealed six distinct configurations of causal conditions leading to users’ continuance intention, which were further classified into two first-order equifinality solutions. Specifically, the first solution highlights perceived online order and convenience value as core conditions, while the second solution suggests that the importance of different subtypes of perceived functional value varies depending on the presence of other conditions.
Conclusion: This study offers new insights into understanding the continuance intention of theme park apps from a configurational perspective, complementing traditional SEM-based IS behavioral intention research. Additionally, it provides a more nuanced understanding of the drivers of continuance intention by categorizing perceived value into four distinct dimensions and incorporating user features related to IS usage and travel habits. This study offers practical suggestions for the theme park operators to strengthen users’ continued usage intention of the theme park app by providing value-added and personalized app services.